1980
DOI: 10.1042/cs0580001
|View full text |Cite
|
Sign up to set email alerts
|

Vasodepressor Property of the Converting Enzyme Inhibitor Captopril (SQ 14 225): The Role of Factors other than Renin-Angiotensin Blockade in the Rat

Abstract: 1. The peptide converting enzyme inhibitor captopril was given (1.25 mg/kg intravenously) to normal and nephrectomized rats and rats with renovascular and deoxycorticosterone hypertension. 2. Captopril lowered blood pressure to a small extent in normal and nephrectomized rats. Bradykinin infusion in nephrectomized animals, however, potentiated the vasodepressor action of captopril. 3. Captopril produced a major blood pressure fall in the early stages of Goldblatt two-kidney one-clip hypertension: even when hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(29 citation statements)
references
References 10 publications
(7 reference statements)
1
28
0
Order By: Relevance
“…Local ACE inhibition not only blocks the constrictor effect of angiotensin I but also enhances the dilator response to bradykinin in the human forearm [10,27]. ACE inhibitors are effective in experimental and human hypertension in circumstances when circulating renin is low or normal [28][29][30][31], and it has been suggested that the hypotensive response to ACE inhibition may be mediated in part by potentiation of bradykinin either in the circulation or tissues [32]. Animal studies have shown that a bradykinin antagonist (B4147) that is less potent than icatibant can blunt the hypotensive response to ACE inhibition by approximately 40% [33].…”
Section: Discussionmentioning
confidence: 99%
“…Local ACE inhibition not only blocks the constrictor effect of angiotensin I but also enhances the dilator response to bradykinin in the human forearm [10,27]. ACE inhibitors are effective in experimental and human hypertension in circumstances when circulating renin is low or normal [28][29][30][31], and it has been suggested that the hypotensive response to ACE inhibition may be mediated in part by potentiation of bradykinin either in the circulation or tissues [32]. Animal studies have shown that a bradykinin antagonist (B4147) that is less potent than icatibant can blunt the hypotensive response to ACE inhibition by approximately 40% [33].…”
Section: Discussionmentioning
confidence: 99%
“…Converting enzyme inhibitors such as Captopril and Teprotide may raise intrarenal concentrations of bradykinin and prostaglandins (Marks, Bing, Thurston & Swales, 1980) which may then be responsible for changes in renal function. At present, however, the weight of evidence favours the proposal that the renal responses are largely due to decreased angiotensin II (A II) production (Hollenberg, 1982 (Freeman, Davis, Lohmeier & Spielman, 1977), infusion of this analogue would also be expected to reverse the actions of Teprotide.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported, however, that the hypotensive effect of CEI is due not only to the blockade of angiotensin converting enzyme but also to stimulation of prostaglandin synthesis (Barr et al, 1980), an increase in kinin (Marks et al, 1980) and a reduction of vasopressin (Igarashi et al, 1985). Thus, such mechanisms might have induced a decrease in B. P. in the present study.…”
Section: Discussionmentioning
confidence: 99%